229 Yeast Proteins Extracted from Saccharomyces Cerevisiae as Alternative Sources of Protein in Swine Nutrition. (8th October 2021) - Kiros, Tadele G; Nadege, Richard; Marden, Jean Philippe; Kuhn, Geraldine; Catunda, Fabio
Abstract: Proteins obtained from microbial biomass like bacteria, yeast, and algae, coined as single cell proteins (SCP), are considered as new and unconventional sources of protein supply both for animal and human use. These microbes convert low value by-products and wastes into protein rich biomass through the process of fermentation. In this regard, yeast was the first microorganism used as source of protein in animal feed. Different industrial methods including plasmolysis, autolysis or enzyme digestions are used to extract the protein rich inner content of a yeast cell known as yeast extract (YE). The protein content of YE may vary depending on the method of extraction, but generally ranges between 50–60% and contains free amino acids and functional peptides. In swine the weaning transition is a critical period where piglets are exposed to different kinds of stresses including the abrupt change from milk to solid feed. To match the highly digestible and protein rich diet in milk, pig producers are using a highly complex diet containing animal products including spray-dried porcine plasma (SDPP) in the pre-starter diet. However, the use of animal products is under scrutiny for biosecurity reasons and SCP from yeast are emerging as good alternatives to replace animal products in piglet diets. Reports from various studies have shown proteins from YE can provide highly digestible proteins with good profile amino acids. Furthermore, it has been shown that yeast proteins improve health and performance of pigs by enhancing immunity and strengthening gut integrity of weaning piglets. Moreover, comparative animal studies in weaned piglets confirmed no significant difference between SDPP and YE proteins in energy content, AA composition, as well as apparent and standardized ileal digestibility of AA suggesting that SCP from yeast could be a good alternative to replace SDPP in weanling piglet diets.